PENGGUNAAN METODE JARING UNTUK MENGURANGI SERANGAN HAMA BURUNG DI DESA SIDOKEPUNG KECAMATAN BUDURAN KABUPATEN SIDOARJO - Rafli Anggarda Prayogi; Bena Azizah; Mirza Andrian Syah (LPPI UMN AL WASHLIYAH, 2025)
One type of pest that can damage, eat, and disrupt the production process of rice plants is bird pests. Pest attacks on rice plants, both directly and indirectly, can cause a significant decrease in production. One method of pest control that can be applied effectively by farmers is the installation of nets on rice plants. This community service activity was carried out in Sidokepung Village, Buduran District, Sidoarjo Regency with the aim of knowing the application of nets on rice panicles as a protection against bird attacks, as well as evaluating the impacts caused after its application. The implementation method was carried out in a participatory and educational manner through direct demonstrations. The results of the activity showed that technically, net installation was carried out by covering the top of the rice plant using nets to prevent birds from entering, while still allowing sunlight and air circulation to reach the plants. The use of nets was able to suppress bird populations, reduce damage to panicles, and significantly increase yields. Although the initial cost of installation is relatively high, this method has proven effective and worthy of wider development because it is environmentally friendly and supports the efficiency of farmers' work time.